Desain Kurikulum yang Inovatif Meningkatkan Kemampuan Siswa di Era Digital : Penelitian - Nurhalizah; Rifa Zairah; Helsi Perlindia; Fadillah Azahra; Abdurrahmansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The rapid digital transformation in education demands innovative curriculum design that aligns with 21st-century competencies. A digital innovative curriculum serves as a key strategy to enhance students’ critical thinking, creativity, collaboration, and communication skills in facing digital-era challenges. This study aims to analyze the role and effectiveness of an innovative digital curriculum in improving students’ abilities in the digital era. The method used is a literature review by examining recent studies on technology-based curriculum models and competency-based learning. The findings indicate that implementing an innovative digital curriculum that integrates information technology, project-based learning, and authentic assessment can improve students’ digital literacy, learning autonomy, and creativity. Therefore, an innovative digital curriculum plays an essential role in shaping adaptive, productive, and competent learners ready to face global technological developments.